جريمة الخطف بقصد الاعتداء على العرض في القانون السوري (دراسة تحليلية) - أوتاني صفاء; نصر مهيب (Latakia University Journal - Economic and Legal Sciences Series, 2018)
The crime of kidnapping of the ugliest and most serious violation of human rights crime, as the impact is not confined to the victim but also to his family and his community, loses kidnapped his liberty, and the suffering his family and relatives of sadness, anxiety and fear for their fate, and get the community in security and tranquility, and becomes a man obsessed with the disappearance of control on the minds of the persons and cripples their movement. The crime of kidnapping and objectives have evolved depending on the evolution of crime methods, and objectives. And that was the crime of kidnapping is characterized more than other crimes, they take picture of different, has been implemented for the goals of multiple goals, different motives, and the crime of kidnapping, the subject of our study takes the most dangerous of those forms, the offender assaults in the crime of kidnapping the purpose of the attack on offer on the freedom of the victim in the movement, also infringes on the freedom of nationality, so is the special nature of this crime, depending on the magnitude of their effects, and therefore the legislature that surrounded with special care, for Adri risk of falling and to avoid to be relations sexual way to moral corruption, disease, physical and psychological, and the dissolution of the family, reflecting in the end on the individual and society. For decades Syrian legislator re-mained sufficient texts that criminal-ize kidnapping intent to assault Alol-rdh display in the Syrian Penal Code promulgated by legislative decree no. 148 of 1949 under the offences against the morals and ethics. But high rates of commission of the crime, and the spread of this phenomenon in light of the Syrian crisis, prompted us to seek to extend the adequacy and appropriateness of these texts, especially that this crisis brought with it new pictures and motives for committing this crime. تعد جريمة الخطف من أبشع الجرائم وأكثرها خطورة وانتهاكاً لحقوق الإنسان، حيث أن تأثيرها لا ينحصر بالمجني عليه بل يتعداه الى أهله وذويه ومجتمعه. يفقد المخطوف حريته، ويعاني أهله وذويه من الحزن والقلق والخوف على مصيره، ويصاب المجتمع في أمنه وطمأنينته، حيث يعم الخوف والذعر ويصبح اختفاء الإنسان هاجس يسيطر على عقول الأشخاص ويشل حركتهم. تطورت جريمة الخطف وأهدافها تبعاً لتطور أساليب الإجرام، وأهدافه، وإن كانت جريمة الخطف تتميز أكثر من غيرها من الجرائم أنها تتخذ صوراً مختلفة، وقد تنفذ من أجل أهداف وغايات متعددة، وبدوافع مختلفة، وجريمة الخطف موضوع دراستنا تأخذ أخطر تلك الصور، فالجاني يعتدي في جريمة الخطف بقصد الاعتداء على العرض على حرية المجني عليه في التنقل، كما يعتدي على حريته الجنسية، لذا تعد هذه الجريمة ذات طابع خاص، تبعاً لجسامة آثارها، ولذا على المشرع أن يحيطها بعناية خاصة، ليدرئ خطر وقوعها، ولتفادي أن تكون العلاقات الجنسية سبيلاً الى الفساد الأخلاقي والأمراض البدنية والنفسية وانحلال العائلة، مما يعكس في النهاية على الفرد والمجتمع. ولعقود طويلة بقي المشرع السوري مكتفياً بالنصوص التي تجريم الخطف بقصد الاعتداء على العرض الواردة في قانون العقوبات الصادر بالمرسوم التشريعي رقم /148/ لعام /1949/ ضمن الجرائم الواقعة على الأخلاق والآداب العامة. ولكن ارتفاع معدلات ارتكاب الجريمة، وتفشي هذه الظاهرة في ظل الأزمة السورية، دفعنا الى البحث بمدى كفاية وملاءمة هذه النصوص، وخاصة أن هذه الأزمة حملت معها صوراً وبواعث جديدة لارتكاب هذه الجريمة.